Evaluation of satisfaction level of tourists in Maliau Basin conservation area / Albinus Ongkudon - Ongkudon, Albinus (Perpustakaan Tun Abdul Razak UiTM Caw Sabah, 2007)
Nature based tourism is the fastest growing segment of the tourism industry because there is a trend towards an increased specialization among tourists. This study was conducted in Maliau Basin Conservation Area (MBCA), A newly establish popular destinations. The objective of this paper is to present findings of the factors that contribute to visitors' level of satisfaction towards ecotourism products and services in MBCA, among the local and international visitors. The findings of the study indicate that price, product, promotion and place were found to be significant factors contributing to visitors' satisfaction. The profile of among local and international visitors in Maliau Basin were examined for association with their socio-demographic and visit characteristics such as gender, age, marital status, education level, occupation, and length of stay. The findings also show that the most popular activities that both local and international respondents wanted to spend during their leisure time adventure trekking, visiting the spectacular waterfalls and the flora on MBCA. The result from this study could, assist the MBCA management to better improve its quality of products and services.